Workplace Safety based on the Hierarchy of Control-A Short Review - Siti Amira Othman (Enhanced Knowledge in Sciences and Technology, 2022)
Workplace safety is an important issue that need to be taken seriously by all workers at the workplace. It is responsibility of safety and health management ultimately rests with the employer to provide safe work environment for the workers. This review paper focusing on how the safety at the workplace can be archived based on the control measure that is commonly used in lessening workers with accidents and injuries exposure. Workplace safety can be established by following the hierarchy of control which proposed to reduce risks and hazards at the workplace. In choosing the appropriate control according to the hierarchy of control measure can be able to help employers in control the occurrence of risks and hazards in the workplace.